Pengaruh Persepsi, Pengetahuan Akuntansi, dan Skala Usaha terhadap Pengggunaan Sistem Informasi Akuntansi Pada Usaha Mikro, Kecil, dan Menengah - Putri, Rizky Rahmalia; Effendi, Syahril (LPPM Universitas Putera Batam, 2023)
This study aims to determine the effect of the effect of MSMES Actors perceptions of accounting on the use ofaccounting information system, the effect of accounting knowledge on the use of accounting informationsystem, and the effect of business scale on the use of accounting information system. The sample of thisresearch is SMEs in the city of Batam as many as 100 SMES. The hypothesis testing technique used ismultiple linear regression and multiple coefficients of determination, which are used to measure the effect ofmore than one independent variable on the depent variable through the validity and reliability test stages, theclassical assumption test of multicollinearity, heteroscedasticity, auto corellation, t test; F test. The result ofthus research indicate that (1) there is no positive influence of the perception of MSME actors on the use ofaccounting information system. (2) there is no positive effect of accounting knowledge on the use of accountinginformation system. (3) there is a positive effect of business scale on the use of accounting information system.(4) there is a positive influence on the perception of MSME actors about accounting, accounting knowledge,and business scale on the use of accounting information system.